Relationship of Genetic Type of Shiga Toxin to Manifestation of Bloody Diarrhea due to Enterohemorrhagic Escherichia coli Serogroup O157 Isolates in Osaka City, Japan - Nishikawa, Y. (American Society for Microbiology, 2000)
One hundred sixty-nine strains of enterohemorrhagic Escherichia coli serogroup O157 were examined for the correlation between the genotype of their Shiga toxin genes (stx) and manifestation of bloody diarrhea (BD). It was shown that the strains carrying only stx2vha were probably less virulent and caused BD less frequently.